Pendekatan Deep Learning dalam Pembelajaran Pendidikan Agama Islam - Syifa Nurul Qolbiah; Pradina Arief Budiman; Nazhif Azwan Albany; Endi Suhendi (Jurnal Dirosah Islamiyah, 2025)
Islamic Religious Education (PAI) plays a crucial role in forming students' holistic character, encompassing intellectual, spiritual, and emotional dimensions. However, PAI implementation often faces methodological constraints, primarily due to a one-way, rote-learning approach that neglects meaningful dialogue, contextual understanding, and value internalization. This approach is also reflected in evaluation systems that prioritize cognitive achievement, often overlooking affective, reflective, and psychomotor aspects. In the context of 21st-century educational challenges, the learning paradigm demands a fundamental shift from teacher-centered to student-centered models, emphasizing active and contextual meaning construction. This shift necessitates participatory, dialogic, and integrative methods where students are active agents in building understanding and life values.This research examines the relevance and potential of integrating deep learning in PAI instruction to enhance the effectiveness and relevance of the educational process. Through a literature review, it was found that deep learning is built upon three pillars: mindful learning, meaningful learning, and joyful learning, which align with the concept of tafaqquh fi al-din (deep understanding of religion). This approach promotes profound conceptual understanding, value internalization, the development of critical and reflective thinking, increased spiritual awareness, and enhanced learning motivation. Strategies such as Problem-Based Learning, Project-Based Learning, Inquiry Learning, Contextual Teaching and Learning, and Storytelling are highly suitable for implementation.While deep learning offers significant benefits in fostering adaptive and virtuous individuals (insan kamil), its implementation faces various challenges, including uneven teacher competence, time limitations, low student motivation, lack of contextual and digital learning media, a prevailing rote-learning culture, curriculum policy inconsistencies, technological access gaps, and difficulties in objectively assessing affective and spiritual aspects. This research recommends integrating deep learning as a framework for developing a transformative, contextual, and student-centered PAI curriculum to prepare a generation that is intelligent, possesses integrity, and is ready to compete in the global era.